Medidas diretas na avaliação da exposição biomecânica de trabalhadores em ambiente real - Locks Neto, Francisco (2016)
The use of objective measurements to quantify biomechanical exposure of workers in real environment has been stimulated by its accuracy and precision. Furthermore, observational methods, self-reports and the use of questionnaires have shown several limitations regarding theirs validity and reliability. Thus, this thesis is composed by three studies in which objective measurements were used to quantify biomechanical exposure of workers in real environment, in two distinct contexts. Study 1 discusses the use of inclinometry, electrogoniometry and electromyography to quantify the biomechanical exposure of industrial workers from the automotive sector, comparing two production lines (one manual and one semiautomated). For this purpose, postures and movements of the head, upper back, upper arms and wrists, as well as the bilateral muscle activity of upper trapezius and wrist extensors were analyzed. Through objective measurements it was possible to identity that the semiautomated line, despite having a higher production rate with less angular velocities, has less opportunities of rest compared to the manual line. Study 2 evaluated the association between time spent standing still with self-report of pain intensity in the lower back and lower extremities (hips, knees and feet/ankles). In this analysis accelerometers were used during four consecutive days to estimate different physical activities performed during work and leisure. It was observed that time spent standing still, quantified by objective measurements, is associated with pain in lower back, hips and knees. Furthermore, time spent standing still during leisure was associated with pain in those three body regions. Throughout objective measurements used in real situations, it was possible to identify biomechanical risk factors in the three developed studies. Based on the findings of those studies, as well as the current literature, there is a need to use direct measurements to quantify the biomechanical exposure of workers in real environment. This method, apart from presents more accuracy and less biases, allows us to identify more representative measurements of the studied population, which allows an intervention properly directed to the real needs of the workers. Therefore, the use of direct measurements to assess biomechanical exposure of workers in real environment needs to be encouraged.